The Gut Microbiota and Epigenetics - Lundstrom, Kenneth (Journal of Nutritional Therapeutics, 2016)
The human gut microbiota presents a strong influence on health and disease development. Metagenomic analysis has revealed the importance of the interaction between the genomes of food, gut microbiota and the host. Also, the establishment of humanized mouse gut microbiota in appropriate animal models has further contributed to the understanding of its function. The composition of the gut microbiota presents a significant impact on the risk of disease development supported by findings of substantial individual variations. Many low molecular weight bacterial substances have been indicated to affect chromatin remodeling, regulation of apoptosis, cellular differentiation and inflammation. The gut microbiota has also been linked to the etiology of cancer because of how it can alter dietary exposures. Furthermore, microbial metabolites have been associated with epigenetic modifications, reversible heritable changes in gene expression without alterations in the primary DNA sequence, which may influence the risk of various cancers and other diseases. As many microbial metabolites are absorbed into systemic circulation, gene expression might also be affected in distal regions of the gut. Therefore, the interaction of dietary intake, gut microbiota and epigenetic modifications plays an important role in disease risk, development and prevention.